Sterol 14α-demethylase mutation leads to amphotericin B resistance in Leishmania mexicana - Mwenechanya, Roy; Kovarova, Julie; Dickens, Nicholas J.; Mudaliar, Manikhandan; Herzyk, Pawel; Vicent, Isabel M.; Weidt, Stefan K.; Burgess, Karl E.; Burchmore, Richard J.S.; Pountain, Andrew W.; Smith, Terry K.; Creek, Darren J.; et al. (Public Library of Science, 2017)
Amphotericin B has emerged as the therapy of choice for use against the leishmaniases. Administration of the drug in its liposomal formulation as a single injection is being promoted in a campaign to bring the leishmaniases under control. Understanding the risks and mechanisms of resistance is therefore of great importance. Here we select amphotericin B-resistant Leishmania mexicana parasites with relative ease. Metabolomic analysis demonstrated that ergosterol, the sterol known to bind the drug, is prevalent in wild-type cells, but diminished in the resistant line, where alternative sterols become prevalent. This indicates that the resistance phenotype is related to loss of drug binding. Comparing sequences of the parasites’ genomes revealed a plethora of single nucleotide polymorphisms that distinguish wild-type and resistant cells, but only one of these was found to be homozygous and associated with a gene encoding an enzyme in the sterol biosynthetic pathway, sterol 14α-demethylase (CYP51). The mutation, N176I, is found outside of the enzyme’s active site, consistent with the fact that the resistant line continues to produce the enzyme’s product. Expression of wild-type sterol 14α-demethylase in the resistant cells caused reversion to drug sensitivity and a restoration of ergosterol synthesis, showing that the mutation is indeed responsible for resistance. The amphotericin B resistant parasites become hypersensitive to pentamidine and also agents that induce oxidative stress. This work reveals the power of combining polyomics approaches, to discover the mechanism underlying drug resistance as well as offering novel insights into the selection of resistance to amphotericin B itself.